The rhetoric of episcopal displacement in the construction of the image of the bishop in Late Antiquity - Figueiredo, Daniel de (Romanitas - Revista de Estudos Grecolatinos, 2019)
Review of: BARRY, J. Bishops in flight: exile and displacement in Late Antiquity. Oakland: University of California Press, 2019. 224 p.
Keywords: Late Antiquity; Exile; Episcopate